LOWER URINARY TRACT INFECTION CAUSES POST-RENAL AZOTEMIA IN MIXED PERSIAN CATS - Pridayanti, Ni Kadek Nila; Anthara, Made Suma; Widyastuti, Sri Kayati (Buletin Veteriner Udayana, 2023)
Azotemia is an increase in the concentration of non-protein nitrogenous compounds in the blood, which consist of urea and creatinine. Azotemia can be categorized into prerenal, renal, and postrenal mechanisms. Postrenal azotemia is a urological condition caused by lower urinary tract disorders. Lower urinary tract infections prevent the normal collection and excretion of urine from the body. This paper reports the case of a mixed-breed Persian male cat named Abu, aged 1.5 years, with dark gray hair, weighing 4.19 kg, brought to the clinic with clinical signs of lethargy and weakness (lethargic), high frequency of urination but little urine (pollakiuria), bloody urine (hematuria), pain during urination (stranguria), and urinary bladder distension (VU) and decreased appetite. Radiographic examination shows enlargement of the size of the VU. Urinalysis examination using a dipstick test showed protein +1, erythrocytes +2 (50), leukocytes +2 (75), pH 7, and urine specific gravity (USG) 1.040. Sedimentation examination obtained results in the form of reddish urine, white froth, the presence of sediment, and the smell of urine. Microscopic examination revealed crystals of magnesium ammonium phosphate (struvite). Routine hematological examination shows an increase in neutrophils (neutrophilia) interpreted as an acute inflammatory response. Blood biochemical examination showed an increase in creatinine and Blood Urea Nitrogen (BUN). The Symmetric Dimethylarginine Assay (SDMA) test yielded 19 ?g/dL. The cat was diagnosed with postrenal azotemia due to lower urinary tract infection. The therapy given is fluid therapy, antibiotics, multivitamins, changing the feed diet, and rinsing with the help of a urinary catheter. Six weeks after recovery, biochemical analysis as azotemia parameters returned to normal values. Detection of postrenal azotemia with prompt and accurate judgment is important for patient recovery.